Biological function of Klebsiella variicola and its effect on the rhizosphere soil of maize seedlings - Lijuan Yang; Kejun Yang (PeerJ, 2020)
Background Deterioration of the ecological environment in recent years has led to increasing soil salinization, which severely affects the cultivation of agricultural crops. While research has focused on improving soil environment through the application of pollution-free microbial fertilizers, there are relatively few plant growth-promoting bacteria suitable for saline-alkali environments. Although Klebsiella variicola can adapt to saline-alkali environments to successfully colonize rhizosphere microenvironments, only a few studies have investigated its role in promoting crop growth. Its effect on the crop rhizosphere soil microenvironment is especially unclear. Methods In this study, the biological function of K. variicola and its colonization in maize seedling rhizosphere soil were studied in detail through selective media and ultraviolet spectrophotometry. The effects of K. variicola on the rhizosphere soil microenvironment and the growth of maize seedlings in saline-alkali and neutral soils were systematically analysed using the colorimetric method, the potassium dichromate volumetric method, and the diffusion absorption method. Results Our results showed that K. variicola played a role in indole acetic acid, acetoin, ammonia, phosphorus, and potassium production, as well as in nitrogen fixation. A high level of colonization was observed in the rhizosphere soil of maize seedlings. Following the application of K. variicola in neutral and saline-alkali soils, the nutrient composition of rhizosphere soil of maize seedlings increased in varying degrees, more notably in saline-alkali soil. The content of organic matter, alkali-hydrolysable nitrogen, available phosphorus, available potassium, alkaline phosphatase, sucrase, urease, and catalase increased by 64.22%, 117.39%, 175.64%, 28.63%, 146.08%, 76.77%, 86.60%, and 45.29%, respectively, insaline-alkalisoil. Conclusion K.variicola, therefore, performed a variety of biological functions to promote the growth of maize seedlings and effectively improve the level of soil nutrients and enzymes in the rhizosphere of maize seedlings, undersaline-alkali stress conditions. It played an important role in enhancing the rhizosphere microenvironment of maize seedlings under saline-alkali stress.